DIRECT REVENUE ALLOCATION TO NIGERIAN LOCAL GOVERNMENTS: A MEANS TO NATIONAL DEVELOPMENT - Nidiya, Sani Adamu; Isa, Dominic Dzari; Medugu, Amos Rapael (IJRDO - Journal of Business Management, 2022)
The issue of revenue allocation remains very volatile, crucial and constitutes a major source of political and governmental tension in Nigeria. It has become a subject of hot debate because of the political nature of the exercise. This paper examines the revenue allocation system in Nigeria vis-à-vis the functional and institutional relevance of local government in national development. The paper strongly advocates for a direct revenue allocation to Nigerian local governments; it also identifies roles/functions capable of playing by local governments in national development; and showcases the operational and tactical roles of local government in enhancing national development. Typology of this research work is basically descriptive. Its research method is qualitative. Data for the study came primarily from secondary sources such as textbooks, journals articles, lecture notes, newspapers and academic research projects. This paper reveals the following facts: grassroots’ development is a forerunner of national development; basic social services are mostly needed at grassroots level; local governments afford citizens the opportunities for political participation, political socialization and political education; and local governments are capable of solving the perpetual problems of rural-urban migration, rural transformation and development. This paper assertively concludes that direct allocation of funds to local governments will facilitate promotion of grassroots’ democracy, promotion of economic development, good governance, political accountability, agricultural growth and development, transparency, local freedom, accessibility to local needs, responsiveness to local wishes and initiatives, rural transformation and overall national development.